Financial well-being, risk avoidance and stock market participation. (23rd September 2019) - Sivaramakrishnan, Sreeram; Srivastava, Mala
The purpose of this study is to understand the influences of risk avoidance and financial well-being on the intention to invest in equity products. Risk avoidance - a reflective construct was measured using a seven-item scale while financial well-being, also a reflective construct was measured using an established eight-item scale. Survey data for urban, retail, middle-class investors was collected across four cities in India. This was then analysed using PLS-SEM and it was found that financial well-being and risk avoidance have a negative influence on the intention to invest in equity products. The finding regarding risk avoidance and intention to invest corroborated earlier studies. A counterintuitive finding was that financial well-being or the feeling of financial security does not embolden an investor to invest in the stock markets rather it seems to prove a deterrent for stock market participation. This suggests that financial institutions may need to highlight gaps in financial security of households or use other creative means of communication to increase stock market participation.